Alkali metal resistant, phosphorus resistant and sulfur poisoning resistant scr denitration catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202611044780.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明针对SCR脱硝催化剂抗中毒能力不足、寿命较短的技术问题,提供一种抗碱金属抗磷抗硫中毒SCR脱硝催化剂,采用“载体层-活性层-抗中毒防护层”三层结构,实现“物理拦截+化学吸附+高效催化”协同,同时抵御碱金属、磷、硫复合中毒,催化剂寿命延长2倍
[0026]1、三层梯度结构创新:针对污泥烟气设计“载体层-活性层-抗中毒防护层”三层结构,实现“物理拦截+化学吸附+高效催化”协同,同时抵御碱金属、磷、硫复合中毒,解决现有催化剂单一结构适配性差的问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flue gas denitrification catalyst technology, and relates to an alkali metal-resistant, phosphorus-resistant, and sulfur-resistant SCR denitrification catalyst, its preparation method, and its application, especially in the application of sludge pyrolysis gasification flue gas. Background Technology
[0002] Sludge pyrolysis and gasification is the mainstream technical route for achieving sludge reduction, harmlessness, stabilization, and resource utilization. This process operates under anoxic conditions below 1100℃, and the flue gas composition is complex, containing high concentrations of alkali metals (Na, K), alkaline earth metals (Ca, Mg), phosphorus (P), sulfur (SO2), and water vapor, with the flue gas temperature mostly in the low-to-medium temperature range of 280~350℃.
[0003] Selective catalytic reduction (SCR) denitrification is a core technology for ultra-clean emission of flue gas from sludge pyrolysis gasification, with the catalyst being its core component. Existing SCR catalysts mostly use titanium dioxide as a support, loading active components such as vanadium-tungsten-molybdenum, like the V2O5-WO3 / TiO2 system. However, the complex composition of alkali metals, phosphorus, and sulfur in sludge flue gas can lead to catalyst poisoning and rapid deactivation: alkali metals neutralize Brønsted acid sites on the catalyst surface, generating inert KVO3 and other species, inhibiting NH3 adsorption and activation; phosphorus readily forms phosphates with active components and the support in the catalyst, clogging pores and reducing acidity; SO2 generates ammonium sulfate or metal sulfates, covering active sites in the catalyst and causing sintering deactivation.
[0004] Existing alkali metal resistant catalysts have the following problems: 1) Insufficient resistance to complex poisoning: Most are single-coating or single-active-component structures, only able to cope with single pollutants (such as alkali metals), unable to resist poisoning caused by complex components of "alkali metal + phosphorus + sulfur", and are prone to rapid deactivation in sludge flue gas; 2) Poor pore size and structure adaptability: The catalyst pores are simple and easily blocked by fine particles and phosphate deposits in sludge flue gas, resulting in decreased mass transfer efficiency and significantly reduced activity at medium and low temperatures (280~350℃); 3) Imbalance between activity and stability: Reducing the content of active components to improve the catalyst's resistance to poisoning leads to insufficient denitrification efficiency, while maintaining high catalyst activity is prone to shortening its lifespan due to high-temperature sintering and loss of active components; 4) Lack of scenario-specific design: No dedicated catalysts have been designed for the flue gas temperature and composition characteristics of sludge pyrolysis gasification flue gas, resulting in poor adaptability and difficulty in meeting ultra-clean emission (NOx) requirements. x ≤50mg / m 3 )Require.
[0005] In summary, existing alkali metal resistant catalysts are not designed with synergistic protective structures for the complex composition of "alkali metal + phosphorus + sulfur" in sludge flue gas, resulting in a catalyst lifespan of only 6 to 12 months, far lower than the 3 to 4 years level in the power industry, which significantly increases the operating cost of sludge treatment. Summary of the Invention
[0006] This invention addresses the technical problems of insufficient resistance to poisoning and short lifespan of SCR denitrification catalysts by providing an SCR denitrification catalyst resistant to alkali metal, phosphorus, and sulfur poisoning. It adopts a three-layer structure of "carrier layer - active layer - anti-poisoning protective layer" to achieve synergistic effects of "physical interception + chemical adsorption + high-efficiency catalysis", and resists the combined poisoning of alkali metals, phosphorus, and sulfur, thus extending the catalyst lifespan by 2 times.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides an alkali metal-resistant, phosphorus-resistant, and sulfur-resistant SCR denitrification catalyst, comprising, from the inside out, a support layer, an active layer, and a protective layer. The support layer is a cordierite honeycomb ceramic with a SiO2-TiO2 coating, wherein the loading of the SiO2-TiO2 coating is 8-18%, preferably 12%. The active layer is a MnO-supported... x -CeO2-WO3 composite active ingredient TiO2-ZrO2 carrier, wherein MnO x The loading of the CeO2-WO3 composite active ingredient is 12-22% of the mass of the TiO2-ZrO2 support, preferably 18%. The protective layer is an Al2O3-ZSM-5 coating doped with CeO2, wherein the doping amount of CeO2 is 2-5% of the total mass of the Al2O3-ZSM-5 coating, preferably 3%.
[0009] The present invention provides a carrier layer on the surface of honeycomb cordierite with SiO2-modified TiO2. SiO2 can inhibit the crystal transformation of TiO2, improve sulfur resistance and specific surface area, and provide a stable loading substrate for the active layer.
[0010] The active layer carrier of this invention is a TiO2-ZrO2 composite oxide, whose porous structure improves specific surface area and mass transfer efficiency. ZrO2 can inhibit the sintering of the active component and extend its lifespan. The active component is MnO. x -CeO2-WO3 ternary system, MnO x It provides low-temperature redox sites, CeO2 promotes oxygen migration and NH3 activation, and WO3 enhances thermal stability and acid site density. The three work together to achieve efficient denitrification at 280~350℃.
[0011] The protective layer of this invention is based on an Al2O3-ZSM-5 coating. The porous Al2O3 structure provides physical adsorption and filtration, intercepting large alkali metal salt particles. The ZSM-5 molecular sieve has a microporous structure, which can selectively adsorb phosphorus and sulfur species, preventing them from penetrating into the active layer. The addition of CeO2 as a catalytic agent can catalyze the oxidation of some SO2, reducing the formation of ammonium sulfate, while simultaneously increasing the alkali metal adsorption capacity.
[0012] The thickness of the carrier layer of the present invention is 50~150 μm, which can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm, preferably 80~120 μm, and more preferably 100 μm.
[0013] The thickness of the active layer of the present invention is 80~200 μm, and can be 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, or 200 μm, preferably 120~160 μm, and more preferably 140 μm.
[0014] The thickness of the protective layer of the present invention is 100~300 μm, and can be 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, or 300 μm, preferably 180~220 μm, and more preferably 200 μm.
[0015] In the SiO2-TiO2 coating of the present invention, the SiO2 doping amount is 5~8% of the TiO2 mass, which can be 5%, 6%, 7%, 8%, and preferably 5%.
[0016] In this invention, the molar ratio of TiO2 to ZrO2 in the TiO2-ZrO2 support is 2~4:1, preferably 3:1.
[0017] This invention MnO x -CeO2-WO3 complex active ingredient MnO x The molar ratio of CeO2 to WO3 is 2~4:1~3:1, preferably 3:2:1.
[0018] In the Al2O3-ZSM-5 coating of the present invention, the mass ratio of Al2O3 to ZSM-5 is 1:1 to 3, preferably 1:1.
[0019] Secondly, the present invention provides a method for preparing the above-mentioned alkali metal-resistant, phosphorus-resistant, and sulfur-resistant SCR denitrification catalyst, comprising the following steps:
[0020] 1) Preparation of the carrier layer: The cleaned and dried honeycomb cordierite was immersed in the pre-prepared SiO2-TiO2 sol, dried, and calcined at 400~600℃ for 2~4 h to obtain the carrier layer;
[0021] 2) Preparation of the active layer: Prepare a TiO2-ZrO2 slurry, coat it onto the surface of the support layer, dry it, and calcine it at 400~500℃ for 1~3h to obtain a porous TiO2-ZrO2 support; immerse the porous TiO2-ZrO2 support in a pre-prepared MnO2 solution. x The active layer is obtained by drying the CeO2-WO3 precursor solution and calcining it at 400-600℃ for 2-4 h.
[0022] 3) Preparation of protective layer: Prepare Al2O3-ZSM-5-CeO2 mixed slurry, coat it on the surface of the active layer, dry it, and calcine it at 350~450℃ for 1~3 h to obtain the protective layer;
[0023] 4) Post-treatment: The catalyst is reduced in a H2 / N2 mixture at 200~350℃ for 1~3 h, and then cooled to obtain the finished catalyst.
[0024] Thirdly, the present invention provides the application of the above-mentioned alkali metal-resistant, phosphorus-resistant, and sulfur-resistant SCR denitrification catalyst in the denitrification of flue gas from sludge pyrolysis and gasification.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] 1. Three-layer gradient structure innovation: The three-layer structure of "carrier layer - active layer - anti-poisoning protection layer" is designed for sludge flue gas to achieve synergy of "physical interception + chemical adsorption + high-efficiency catalysis", while resisting the complex poisoning of alkali metals, phosphorus and sulfur, and solving the problem of poor adaptability of existing catalysts with single structure.
[0027] 2. Synergistic effect of anti-complex poisoning materials: The protective layer adopts a mixed system of Al2O3-ZSM-5-CeO2. Al2O3 intercepts alkali metal particles, ZSM-5 selectively adsorbs phosphorus and sulfur, and CeO2 catalyzes the oxidation of SO2 and improves adsorption capacity. The three work together to significantly reduce the risk of complex poisoning.
[0028] 3. Optimization of active components and carriers: The active layer uses MnO x -CeO2-WO3 ternary system, suitable for medium and low temperature sludge flue gas of 280~350℃; the carrier adopts TiO2-ZrO2 composite oxide, the porous structure improves mass transfer efficiency, inhibits the sintering of active components, and balances activity and stability.
[0029] 4. Precise adaptation to specific scenarios: Targeting the characteristics of sludge pyrolysis gasification flue gas with high water content, high alkali metal content, high phosphorus content, and high sulfur content, the pore size distribution and coating thickness are optimized to avoid pore blockage, meet ultra-clean emission requirements, and fill the technological gap of special anti-composite poisoning catalyst for sludge flue gas.
[0030] 5. Reduced operating costs: Catalyst lifespan is extended by 2 times, reducing replacement frequency and hazardous waste disposal costs. A single 100t / d sludge pyrolysis gasification treatment project can save approximately RMB 800,000 to 1.2 million in catalyst and disposal costs annually.
[0031] 6. Reduced energy and ammonia consumption: The medium-low temperature high-efficiency active catalyst does not require flue gas heating, saving approximately 500,000 to 800,000 kWh of energy per year; the high-efficiency catalysis reduces ammonia escape, reducing ammonia consumption by 15 to 20%, and saving approximately 100,000 to 150,000 yuan in reagent costs per year.
[0032] 7. Improve resource utilization efficiency: Stable operation of the catalyst ensures that the sludge pyrolysis gasification system continuously meets the standards, reduces downtime and maintenance losses, extends equipment life, improves overall resource utilization efficiency, and increases annual comprehensive benefits by 10-15%. Detailed Implementation
[0033] The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the test methods in the following embodiments are conventional methods. Unless otherwise specified, all chemical reagents and chemicals mentioned in the following embodiments are chemical reagents and chemicals known and commonly used in the prior art; unless otherwise specified, the percentages in the following embodiments are mass percentages. Unless otherwise specified, the solutions in the following embodiments are aqueous solutions with water as the solvent.
[0034] The cordierite honeycomb carrier used in the following examples has a size of 100 mm × 100 mm × 100 mm and a hole count of 16 holes / cm. 2 The pore size of ZSM-5 molecular sieve is 0.53~0.58 nm.
[0035] Example 1
[0036] (1) Preparation of the carrier layer:
[0037] Preparation of SiO2-TiO2 sol: Tetrabutyl titanate was used as the titanium source, tetraethyl orthosilicate as the silicon source, anhydrous ethanol as the solvent, and glacial acetic acid as the chelating agent. The raw materials were measured at 5% of the mass of SiO2 to TiO2, mixed and stirred for 2 h, and deionized water was slowly added dropwise for hydrolysis. The mixture was then sealed and aged at room temperature for 12 h to obtain a clear and stable SiO2-TiO2 sol.
[0038] After being ultrasonically cleaned with deionized water for 30 min and dried at 120℃ for 2 h, the honeycomb cordierite was completely immersed in SiO2-TiO2 sol for 15 min, drained, dried at 120℃ for 2 h, and calcined at 500℃ for 3 h to obtain a carrier layer with a thickness controlled at 100 μm.
[0039] (2) Preparation of the active layer:
[0040] Preparation of TiO2-ZrO2 slurry with a solid content of 30wt%: Weigh nano-anatase TiO2 and monoclinic ZrO2 powders according to the molar ratio of TiO2 to ZrO2 of 3:1, add deionized water, carboxymethyl cellulose dispersant and silica sol binder, stir at high speed and then sand mill for 2 hours, and add water to adjust the solid content to 30wt%.
[0041] TiO2-ZrO2 slurry was impregnated and coated onto the surface of the carrier layer, drained, dried at 120℃ for 2 h, and calcined at 450℃ for 2 h to obtain a porous TiO2-ZrO2 carrier.
[0042] Preparation of MnO x -CeO2-WO3 precursor solution (Mn:Ce:W molar ratio of 3:2:1): Weigh manganese nitrate, cerium nitrate, and ammonium metatungstate according to the metal molar ratio of 3:2:1, dissolve them in deionized water, stir at room temperature until completely dissolved, and prepare a transparent precursor solution with a total metal ion concentration of 1.2 mol / L.
[0043] Porous TiO2-ZrO2 support is immersed in MnO x The active layer was obtained by immersing the CeO2-WO3 precursor solution for 20 min, drying at 120℃ for 2 h, and calcining at 500℃ for 3 h, with the thickness controlled at 140 μm.
[0044] (3) Preparation of protective layer:
[0045] Preparation of Al2O3-ZSM-5-CeO2 mixed slurry: The mass ratio of Al2O3 to ZSM-5 is 1:1, and CeO2 powder (accounting for 3% of the total mass of powder) is added; deionized water and polyvinyl alcohol binder are added to the powder, ball milling is performed for 3 hours, and water is added to adjust the solid content of the slurry to 25wt%.
[0046] The Al2O3-ZSM-5-CeO2 mixed slurry was uniformly coated on the surface of the active layer, drained, dried at 120℃ for 2 h, and calcined at 400℃ for 2 h to obtain the protective layer with a thickness controlled at 200 μm.
[0047] (4) Post-processing:
[0048] The catalyst was reduced at 300℃ (heating rate 2℃ / min) for 2h in a mixed gas of H2 and N2 with a volume ratio of 5:95, and the finished catalyst was obtained after cooling.
[0049] Example 2
[0050] This embodiment is basically the same as that of embodiment 1, except that the amount of SiO2 in the SiO2-TiO2 sol in step (1) accounts for 8% of the mass of TiO2.
[0051] Example 3
[0052] This embodiment is basically the same as embodiment 1, except that the molar ratio of TiO2 to ZrO2 in the TiO2-ZrO2 slurry in step (2) is adjusted to 2:1.
[0053] Example 4
[0054] This embodiment is basically the same as embodiment 1, except that: the MnO in step (2) x The molar ratio of Mn:Ce:W in the CeO2-WO3 precursor solution was adjusted to 4:2:1.
[0055] Example 5
[0056] This embodiment is basically the same as embodiment 1, except that the amount of CeO2 powder in the Al2O3-ZSM-5-CeO2 mixed slurry in step (2) accounts for 2% of the total mass of the powder.
[0057] The performance test was conducted using the following methods, and the results are shown in Table 1.
[0058] (1) Denitrification efficiency: Tested according to the method specified in "Cellular Flue Gas Denitrification Catalyst" (GB / T 31587-2015). The simulated flue gas composition was: NO concentration of 500 ppm, NH3 / NO x The molar ratio is 1:1, the O2 content is 5%, N2 is the balance gas, and the space velocity is 8000 h⁻¹. -1 The reaction temperature range is 280~350℃. A flue gas analyzer is used to continuously monitor the inlet and outlet NO concentrations. The denitrification efficiency is calculated as η = (1-C) / (2π) * (1 - C ... _out / C _in Calculate by multiplying by 100%.
[0059] (2) Anti-poisoning performance: 2500 ppm SO2 was introduced into the simulated flue gas, and 5 wt% Na / K / Ca / P were co-doped. 12 vol% H2O was continuously run for 300 h for accelerated aging test. After aging, the denitrification efficiency was retested. The tolerance to compound poisoning was evaluated by the denitrification efficiency retention rate (%).
[0060] (3) Mechanical properties: In accordance with the method specified in "Cellular Flue Gas Denitrification Catalyst" (GB / T 31587-2015), the three mechanical properties of the catalyst were tested: axial compressive strength, radial compressive strength, and dust accelerated wear rate over 1000 h.
[0061] (4) Specific surface area: According to the "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method" (GB / T 19587-2017), the low-temperature nitrogen static adsorption method was used for testing; the sample was degassed under vacuum at 200℃ for 2 h to remove adsorbed water and impurities on the surface, and nitrogen adsorption-desorption isotherms were collected under liquid nitrogen isothermal conditions. The specific surface area of the sample was calculated by the BET multi-point method, with the unit being m. 2 / g.
[0062] Table 1 Performance Test Results
[0063]
[0064] As can be seen from Table 1, the catalyst of this invention operates at 280~350℃ with an NH3 / NO content of [missing information]. x =1:1, airspeed 8000 h -1 Under these conditions, NO x Removal efficiency ≥95%, export NO x Concentration ≤35 mg / m 3 It meets the ultra-clean requirements of the "Standard for Pollutant Control of Municipal Solid Waste Incineration" (GB18485-2014); under the conditions of Na / K / Ca / P co-doping 5 wt%, SO2 2500 ppm, and H2O 12 vol%, it can continuously operate for 300 h with a denitrification efficiency decay of ≤20%, which is far superior to conventional catalysts (decay ≥50%); mechanical strength ≥12 MPa, wear rate ≤0.5% / 1000 h, and service life ≥23 months (approximately 20000 h), which is 2 to 3 times that of conventional catalysts; denitrification efficiency ≥90% at 280℃, and is suitable for the medium and low temperature flue gas temperature after sludge pyrolysis and gasification waste heat recovery, without the need for additional heating, thus reducing energy consumption.
[0065] Example 6
[0066] The catalyst prepared in Example 1 was applied to a sludge pyrolysis gasification project with a processing capacity of 1000 t / d. The process route was: sludge pyrolysis gasification furnace → hot blast stove → waste heat recovery → bag filter dust collection → desulfurization → emission meeting standards. The flue gas temperature was 320℃, and the flue gas composition was as follows: NO x 520 ppm, SO2 2500 ppm, alkali metal + phosphorus co-doped 4.5 wt%. The SCR denitrification reactor is packed with the catalyst of this invention at a packing density of 0.72 t / m³. 3 .
[0067] Execution result: NO x Removal efficiency 96.2%, outlet concentration 28 mg / m³ 3After 300 days of continuous operation, the efficiency decreased by 8.5%, and ammonia slip was ≤ 2 ppm. In contrast, conventional V2O5-WO3 / TiO2 catalysts, under the same operating conditions, saw their denitrification efficiency drop to 72% after 300 days, a decrease of 28%. This demonstrates that the catalyst of this invention has significantly better resistance to complex poisoning than existing products.
[0068] The embodiments described above are merely preferred embodiments of the present invention and are only used to explain the present invention. They are not intended to limit the scope of the present invention. For those skilled in the art, other implementation methods can be easily made by substitution or modification based on the technical content disclosed in this specification. Therefore, all changes and improvements made on the principle of the present invention should be included within the scope of the patent application of the present invention.
Claims
1. A SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning, characterized in that, From the inside out, the layers are a carrier layer, an active layer, and a protective layer; the carrier layer is a cordierite honeycomb ceramic with a SiO2-TiO2 coating, and the loading of the SiO2-TiO2 coating is 8-15%; the active layer is a MnO-loaded... x -CeO2-WO3 composite active ingredient TiO2-ZrO2 carrier, wherein MnO x The loading amount of the CeO2-WO3 composite active ingredient is 12-22% of the mass of the TiO2-ZrO2 support; the protective layer is an Al2O3-ZSM-5 coating doped with CeO2, and the doping amount of CeO2 is 2-5% of the total mass of the Al2O3-ZSM-5 coating.
2. The SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to claim 1, characterized in that, The thickness of the carrier layer is 50~150 μm, the thickness of the active layer is 80~200 μm, and the thickness of the protective layer is 100~300 μm.
3. The SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to claim 1, characterized in that, The SiO2 doping amount in the SiO2-TiO2 coating is 5-8% of the TiO2 mass.
4. The SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to claim 1, characterized in that, The molar ratio of TiO2 to ZrO2 in the TiO2-ZrO2 support is 2~4:
1.
5. The SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to claim 1, characterized in that, The MnO x -CeO2-WO3 complex active ingredient MnO x The molar ratio of CeO2 to WO3 is 2~4:1~3:
1.
6. The SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to claim 1, characterized in that, The mass ratio of Al2O3 to ZSM-5 in the Al2O3-ZSM-5 coating is 1:1~3.
7. The preparation method of the SCR denitrification catalyst resistant to alkali metals, phosphorus, and sulfur poisoning according to any one of claims 1 to 6, characterized in that, Includes the following steps: 1) Preparation of the carrier layer: The cleaned and dried honeycomb cordierite was immersed in the pre-prepared SiO2-TiO2 sol, dried, and calcined at 400~600℃ for 2~4 h to obtain the carrier layer; 2) Preparation of the active layer: Prepare a TiO2-ZrO2 slurry, coat it onto the surface of the support layer, dry it, and calcine it at 400~500℃ for 1~3 h to obtain a porous TiO2-ZrO2 support; immerse the porous TiO2-ZrO2 support in a pre-prepared MnO2 solution. x The active layer is obtained by drying the CeO2-WO3 precursor solution and calcining it at 400-600℃ for 2-4 h. 3) Preparation of protective layer: Prepare Al2O3-ZSM-5-CeO2 mixed slurry, coat it on the surface of the active layer, dry it, and calcine it at 350~450℃ for 1~3 h to obtain the protective layer; 4) Post-treatment: The catalyst is reduced in a H2 / N2 mixture at 200~350℃ for 1~3 h, and then cooled to obtain the finished catalyst.
8. The application of the alkali metal resistant, phosphorus resistant, and sulfur resistant SCR denitrification catalyst according to any one of claims 1 to 6 in the denitrification of flue gas from sludge pyrolysis and gasification.